GH receptor polymorphisms guide second-line therapies to prevent acromegaly skeletal fragility: preliminary results of a pilot study - Chiloiro, Sabrina; Costanza, Flavia; Giampietro, Antonella; Infante, Amato; Mattogno, Pier Paolo; Angelini, Flavia; Gullì, Consolato; Lauretti, Liverana; Rigante, Mario; Olivi, Alessandro; De Marinis, Laura; Doglietto, Francesco; et al. (Frontiers in Endocrinology, 2024)
Background: Skeletal fragility is characterized by increased frequency of vertebral fractures (VFs) in acromegaly. Several trials were conducted to identify modifiable risk factors and predictors of VFs, with limited data on the prognostic role of GH receptor (GHR) isoforms. In this study, we investigated the potential role of GHR polymorphism on the occurrence of incidental VFs (i-VFs), in patients treated with second-line medical therapies.Methods. A longitudinal, retrospective, observational was conducted on a cohort study on 45 acromegalic patients not-responsive to first-generation somatostatin receptor ligands (fg-SRLs) and treated with GHR antagonist (Pegvisomant) or with the second-generation SRLs (Pasireotide longacting release).Results. Second line treatments were Pegvisomant plus fg-SRLs in 26 patients and Pasireotide LAR in 19 patients. From the group treated with fg-SRLs+Peg-V, the fl-GHR isoform was identified in 18 patients (69.2%) and the d3-GHR isoform in 8 patients (30.8%). I-VFs arose exclusively in fl-GHR isoform carriers (p=0.039). From the group treated with Pasireotide LAR, the fl-GHR isoform was identified in 11 patients (57.9%), and the d3-GHR isoform in 8 patients (42.1%). I-VFs arose exclusively in d3-GHR isoform carriers (p=0.018). Patients with fl-GHR isoform had a higher risk for i-VFs if treated with fg-SRL+Peg-V (OR: 1.6 95%IC: 1.1-2.3, p=0.04), and a lower risk if treated with Pasi-LAR (OR: 0.26 IC95%: 0.11-0.66, p=0.038).Conclusions. Our data support a predictive role of the GHR isoforms for the occurrence of i-VFs in acromegalic patients treated with second-line drugs, tailored to the individual patient. The knowledge of the GHR polymorphism may facilitate the choice of second-line therapies, improving the therapeutic approach, in the context of personalized medicine.